Three Cases of Bilateral Breast Absence Associated with Familial Congenital Ectodermal Defects - Su S; Xie R; Ding X; Lin Y (Dove Medical Press, 2021)
Shunqing Su, Rurong Xie, Xiumei Ding, Yuechun Lin Department of Burn & Plastic Surgery, Dalang Hospital of Dongguan, Dongguan, 523770, People’s Republic of ChinaCorrespondence: Shunqing SuDepartment of Burn & Plastic Surgery, Dalang Hospital of Dongguan, No. 85 of Jinlang Middle Street, Dalang Town, Dongguan, 523770, People’s Republic of ChinaTel +86 769 83009512Fax +86 769 83009171Email sushunqing_dr88@163.comObjective: This study aims to analyze three cases of bilateral breast absence associated with congenital ectodermal defects in the same family to identify a suitable clinical treatment plan.Methods: Three patients (case 1 and case 2 are a brother–sister relationship; case 3 is their father) complained of the absence of breasts, nipples, and areolas, accompanied by deformity of facial features and fingers; all other clinical indexes were normal. Case 1 first underwent bilateral papillary reconstruction, with areola embroidery carried out six months later. Case 2 first underwent prosthetic breast augmentation, and after ten months, she underwent nipple reconstruction and auricular cartilage, silica gel prosthesis rhinoplasty, epicanthus correction, and areola embroidery. Gene tests were carried out for both cases. Case 3 did not undergo any surgical procedures.Results: The operations achieved good results, although in case 2, the reconstructed nipples retracted and became smaller. Neither of the subjects had adverse reactions after the procedures. A heterozygous mutation of the KCTD1 gene c.2020A>T (p.i674f), a mutation inherited from case 3 (their father), was detected through gene analysis. Copy number analysis and single-nucleotide polymorphism (SNP) analysis were carried out, but no copy number variation possibly related to clinical manifestations was detected.Conclusion: The bilateral breast absence associated with familial congenital ectodermal defects in cases 1 and 2 were found to be induced by a heterozygous mutation of the KCTD1 gene c.2020A>T (p.i674f) inherited from case 3 (their father). Two of the three cases underwent surgical treatment, and good clinical results were achieved.Keywords: bilateral breast absence associated with congenital ectodermal defects, familial inheritance, breast reconstruction, nipple reconstruction, case report